Kinetic studies on carbon dioxide capture using lignocellulosic based activated carbon - Rashidi, N.A. (Elsevier Ltd, 2013)
CO2(Carbon dioxide) emissions are one of the greenhouse gases that cause global warming. The power generation industry is one of the main emitters of CO2, and the emissions are expected to increase in the coming years as there seems to be no abatement in the consumption of fossil fuels for the production of electricity. Thus, there is a need for CO2 adsorption technologies to mitigate the emissions. However, there are several disadvantages associated with the current adsorption technologies. One of the issues is corrosion and the need for specialized equipment. Therefore, alternative and more sustainable materials are sought after to improve the viability of the adsorption technology. In this study, several types of agricultural wastes were used as activated carbon precursors for CO2 adsorption process in a TGA (thermogravimetric analyser). The adsorption was also modelled through a pseudo-first order and second order model, Elovich's kinetic model, and an intra-particle diffusion model. From the correlation coefficient, it was found that pseudo-second order model was well-fitted with the kinetic data. In addition, activation energy below than 42kJ/mol confirmed that the physisorption process occurred. Â© 2013 Elsevier Ltd.